STUDI PEMANFAATAN INTERNET PADA MAHASISWA KOMUNIKASI FISIP UNTAD ANGKATAN 2015 - Haikal, Muhammad; Zainuddin, Sumarni; Alatas, Raisa (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2019)
Along with the change in the learning paradigm, the success of teaching and learning activities in higher education is not only determined by the factor of the lecturer, but is strongly influenced by the activity of students. Through the internet, students can access various literatures and scientific references that are needed quickly, so as to facilitate the study process. The problem of this research is how to use the internet by students of Fisip Untad Communications class of 2015, and what factors support students of Fisip Untad Communications to use the internet as a medium. This research uses qualitative research with a case study approach. There were four informants in this study. Data collection techniques are observation and interviews. The results showed that some Untad Communication students were familiar with and used the internet as a medium. Each student has a different way of using the internet such as where to access, how long to access the internet, and also the sites accessed by students. The places to access the internet that are often used by students are in internet cafes, at home, and in the environment around campus. Untad Fisip Communications students use the internet as a medium, because the internet can make it easier to find information and course assignments. Factors supporting the use of the internet as a student medium include demands from lecturers to fulfill course assignments, more complete learning resources on the internet, assisting in obtaining course references, making it easier to do assignments, the information available is clearer and more valid, faster in information search, more complete sources of knowledge, hotspots on campus, up to date/new news, lower costs, easy access, curiosity and needs.